2009
DOI: 10.1016/j.bmc.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic latrunculin B analogs: Studies of actin docking support a proposed mechanism for latrunculin bioactivity

Abstract: Latrunculins are unique macrolides containing a thiazolidinone moiety. Latrunculins A, B and T and 16-epi-latrunculin B were isolated from the Red Sea sponge Negombata magnifica. N-alkylated, Omethylated analogs of latrunculin B were synthesized and biological evaluation was performed for antifungal and antiprotozoal activity. The natural latrunculins showed significant bioactivity, while the semisynthetic analogs did not. Docking studies of these analogs into the X-ray crystal structure of G-actin showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…Latrunculin T has shown superior antifungal activity against Saccharomyces cerevisiae compared to either of the macrolides latrunculin A or B. 40 Interestingly 14 displayed activity in Table 1 against the parasite T. brucei but did not disrupt MF assembly at 20 µg/mL suggesting a mode of action independent of the actin pathway similar to reports by others. 27, 42 …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Latrunculin T has shown superior antifungal activity against Saccharomyces cerevisiae compared to either of the macrolides latrunculin A or B. 40 Interestingly 14 displayed activity in Table 1 against the parasite T. brucei but did not disrupt MF assembly at 20 µg/mL suggesting a mode of action independent of the actin pathway similar to reports by others. 27, 42 …”
Section: Resultssupporting
confidence: 72%
“…27 Other latrunculin analogs have also recently emerged as potential anti-tumor, anti-microbial, anti-fungal, and anti-protozoal therapeutic leads. 27, 4043 …”
Section: Resultsmentioning
confidence: 99%
“…Studies on semisynthetic latrunculin analogues revealed that N-alkylated derivatives are inactive. 20 Carbonate derivatives of 17-OH (hemiacetal OH) display reduced affinity to actin. 21 Due to the convergent synthetic strategy used by the Fürstner group twelve latrunculin analogues could be prepared that addressed the role of the methyl groups in the macrocyclic ring and the configurations in the thiazolidinone ring.…”
Section: Latrunculin Analoguesmentioning
confidence: 99%
“…In 2008, Crews and co-workers reported the isolation, characterization, and initial biological assessment of a series of new, naturally occurring latrunculin analogues. 14 One compound, (+)-18- epi -latrunculol A ( 1 ), exhibited selective solid tumor cytotoxicity when tested against HCT-116 (5.5 μM) and MDA-MB-435 (>50 μM), but unlike the other members of the latrunculin family, 1 was devoid of the ability to inhibit actin polymerization. On the other hand, the parent compounds (+)-latrunculin A ( 2 ) and B ( 3 ) demonstrate nonselective cytotoxicity profiles, thus limiting their use as chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%